Implementation of Smart Receptacle Based on The Internet of Things as Developing The Quality of Micro, Small and Medium Enterprises - Dona Tiara Lubis (G-Tech: Jurnal Teknologi Terapan, 2025)
The phenomenon of "chargers" is where visitors come to a cafe just to charge their smartphones or laptops without ordering food or drinks. This condition is becoming more prevalent due to various variables, including the rising utilization of smartphones and laptops, the necessity to charge devices while traveling, and cafés becoming the primary charging option due to their complimentary Wi-Fi and a conducive environment. The Smart Receptacle is a power outlet utilizing an ESP8266 microprocessor, capable of monitoring electric current and calculating use fees depending on a predefined program. This product utilizes the Internet of Things (IoT) to facilitate real-time monitoring of electric current via electronic devices. Smart Receptacle provides a solution for MSMEs, primarily targeting the Food & Beverage sector, while it is equally applicable to other industries necessitating efficiency and control in electricity consumption. This instrument can quantify the power utilized and compute the electricity consumption of each electrical gadget employed.